The Holiday - Green, Jane ; Coburn, Jennifer and Ireland, Liz (London Penguin Books, 2012)
If you had one wish this Christmas, what would it be? Sarah wishes not to be lonely. She shouldn't be - not with Eddie, her husband, and their two children by her side ...but since Sarah waved farewell to the bright lights of the big city and moved to a picture perfect home in the country, her marriage is missing its usual sparkle.
Keywords: Romance fiction, American